2022
DOI: 10.1155/2022/3049994
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and α-Glucosidase Inhibitory Activities of Chemical Constituents from Bruguiera parviflora Leaves

Abstract: Bruguiera parviflora (Rhizophoraceae) is one of the Bruguiera genus-based mangrove plants which has not been investigated for the chemical compositions as well as biological activities so far. The present study was aimed at investigating the phytochemicals as well as anti-inflammatory and α-glucosidase inhibitory activities of B. parviflora leaves. The results showed that the crude extract and its fractions significantly increased the percentage inhibitory activity against α-glucosidase and decreased NO produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Taxifolin (also called dihydroquercetin, 24 ) was reported in six studies for its potency to inhibit both α-glucosidase and α-amylase [ 65 , 75 79 ]. The results showed that this compound exhibited comparable inhibitory activity to that of acarbose in the same condition while inhibiting α-amylase more weakly.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Taxifolin (also called dihydroquercetin, 24 ) was reported in six studies for its potency to inhibit both α-glucosidase and α-amylase [ 65 , 75 79 ]. The results showed that this compound exhibited comparable inhibitory activity to that of acarbose in the same condition while inhibiting α-amylase more weakly.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin (68) is a natural polyphenol obtained in more than 50 plant species, as shown in the curated dataset. In terms of α-glucosidase inhibitory potential, quercetin showed superior efficacy compared to acarbose, as demonstrated by 45 out of 65 in vitro studies [ 41 , 51 , 52 , 54 , 61 , 75 , 76 , 83 , 93 95 , 98 , 101 , 105 , 114 , 116 , 141 169 ], making it the most well-examined flavonoid against α-glucosidase. It is worth mentioning that quercetin ( 68 ) was even used as a positive control in several studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations